‘Drought Terroirs’ in Southern Angola - Blanes, Ruy Llera; Cardoso, Carolina Valente; Alicerces Bahu, Helder; Fortuna, Cláudio (Blogal Studies, 2021)
Droughts are global phenomena and must be understood and researched as such. In these anthropocenic times, we are increasingly aware of the scales and networks of climate change and its effects. One such case is the drought cycle experienced in Southern Africa in recent years, generally attributed to a disruption in the annual rainfalls caused by the El Niño climate event. In this framework, the region of Southern Angola has experienced an extreme cycle of drought that has built up on previous cycles and culminated in the disastrous year of 2019, with millions of livestock dead and an estimated 2.3 million people facing food insecurity in the provinces of Cunene, Huila, and Namibe (Amnesty International 2019). The latest UNICEF report on the Angolan Humanitarian situation mentions over 390,000 children screened for malnutrition resulting from the drought (Reliefweb, February 2021).